Characteristics of German Real Estate Return Distributions: Evidence from Germany and Comparison to the U.S. and U.K. - Raimond Maurer; Frank Reiner; Steffen Sebastian (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
In contrast to the United States and the United Kingdom, little empirical work exists about the distributional characteristics of appraisalbased real estate returns outside these countries. The purpose of this study is to fill this gap by focusing on Germany. In line with other studies, this paper offers an extensive investigation into the distribution of German real estate returns and compares them with and U.S. and U.K. data in the same period. Furthermore, the comovements with bonds and stocks are also examined. In the core, the distributional characteristics for German real estate are comparable to that for the U.S. and U.K.
urn:nbn:de:hebis:30-17865
Keywords: 330; Immobilienfonds; Rendite; Index; Gewerbeimmobilien; Schätzung; Großbritannien; USA; Deutschland